2013
DOI: 10.1038/npp.2013.341
|View full text |Cite
|
Sign up to set email alerts
|

Protein Kinase D1-Dependent Phosphorylation of Dopamine D1 Receptor Regulates Cocaine-Induced Behavioral Responses

Abstract: The dopamine (DA) D1 receptor (D1R) is critically involved in reward and drug addiction. Phosphorylation-mediated desensitization or internalization of D1R has been extensively investigated. However, the potential for upregulation of D1R function through phosphorylation remains to be determined. Here we report that acute cocaine exposure induces protein kinase D1 (PKD1) activation in the rat striatum, and knockdown of PKD1 in the rat dorsal striatum attenuates cocaine-induced locomotor hyperactivity. Moreover,… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
24
0

Year Published

2014
2014
2022
2022

Publication Types

Select...
4
2

Relationship

1
5

Authors

Journals

citations
Cited by 21 publications
(24 citation statements)
references
References 48 publications
0
24
0
Order By: Relevance
“…24 hours after the last conditioning session, rats were tested following the same procedure as the preconditioning test (post-conditioning phase). The time spent in each chamber was recorded and CPP was determine by calculating a CPP score (time in paired chamber – time in unpaired chamber (Lax, George, Ignatz, & Kolber, 2014; Wang et al, 2014; Xue et al, 2014)).…”
Section: Methodsmentioning
confidence: 99%
“…24 hours after the last conditioning session, rats were tested following the same procedure as the preconditioning test (post-conditioning phase). The time spent in each chamber was recorded and CPP was determine by calculating a CPP score (time in paired chamber – time in unpaired chamber (Lax, George, Ignatz, & Kolber, 2014; Wang et al, 2014; Xue et al, 2014)).…”
Section: Methodsmentioning
confidence: 99%
“…Cells were used 24 h post-transfection. YFP-D1R and YFP-S421A-D1R plasmids were described previously [9] .…”
Section: Cell Culture and Transfectionmentioning
confidence: 99%
“…Thus, the heterotopic expression of S421A Our recent studies indicated that phosphorylation of the D1R at S421 promotes receptor membrane localization [9] , so we compared the levels of D1R localized in the membrane fractions in the striatum of WT and Tg-S421A mice. The membrane localization of D1R was reduced in Tg-S421A mice compared with WT mice (P <0.05, Fig.…”
Section: Reduced Membrane Localization and Downstream Erk Signaling Omentioning
confidence: 99%
See 2 more Smart Citations